Interference Periods of Weeds in Maize in No-Tillage and Conventional Systems at High Altitudes - E.O. HELVIG; K.K.G. PINHEIRO; A.C. DRANCA; A.A.P. SILVA; M.C. MENDES; C.D.G. MACIEL (Planta Daninha)
ABSTRACT: The objective of this study was to determine the coexistence periods of weeds (CTWR = critical timing of weed removal) and control (CWFP = critical weed-free period) in maize crops in no-tillage and conventional systems at high altitudes in southern Brazil. To this end, four experiments were conducted in Guarapuava-Paraná during the 2016/2017 crop season using P2530™ (conventional) and P3271H™ (transgenic genetically modified for glyphosate tolerance) hybrids in no-tillage and conventional systems with crop residues of black oat (Avena strigosa). The experimental design was a randomized complete block with five repetitions. The treatments were divided into periods of CTWR and CWFP for 0, 7, 14, 28, 42, 63, and 126 days after the emergence of crops (DAE). Among the weeds, only eudicotyledonous species predominated throughout the crop cycle in both production systems. The productivity results established for P2530™ and P3271H™ hybrids in a conventional system with the incorporation of straw in the soil indicated a critical period of weed control (CPWC) from 23 to 39 DAE and 23 to 35 DAE, respectively. For direct sowing (no-tillage system) on black oat straw, no CPWC was established, as it required only one single point of control between the periods of 21 to 33 DAE and 23 to 31 DAE for the P2530™ and P3271H™ hybrids, respectively. The direct sowing in black oat straw constituted an efficient strategy to reduce weed interference and the necessity of weed management practices.